Association between microcephaly, Zika virus infection, and other risk factors in Brazil: final report of a case-control study. Issue 3 (March 2018) - de Araújo, Thalia Velho Barreto; Ximenes, Ricardo Arraes de Alencar; Miranda-Filho, Demócrito de Barros; Souza, Wayner Vieira; Montarroyos, Ulisses Ramos; de Melo, Ana Paula Lopes; Valongueiro, Sandra; de Albuquerque, Maria de Fátima Pessoa Militão; Braga, Cynthia; Filho, Sinval Pinto Brandão; Cordeiro, Marli Tenório; Vazquez, Enrique; et al.
Summary: Background: A Zika virus epidemic emerged in northeast Brazil in 2015 and was followed by a striking increase in congenital microcephaly cases, triggering a declaration of an international public health emergency. This is the final report of the first case-control study evaluating the potential causes of microcephaly: congenital Zika virus infection, vaccines, and larvicides. The published preliminary report suggested a strong association between microcephaly and congenital Zika virus infection. Methods: We did a case-control study in eight public maternity hospitals in Recife, Brazil. Cases were neonates born with microcephaly, defined as a head circumference of 2 SD below the mean. Two controls without microcephaly were matched to each case by expected date of delivery and area of residence. We tested the serum of cases and controls and the CSF of cases for detection of Zika virus genomes with quantitative RT-PCR and for detection of IgM antibodies with capture-IgM ELISA. We also tested maternal serum with plaque reduction neutralisation assays for Zika and dengue viruses. We estimated matched crude and adjusted odds ratios with exact conditional logistic regression to determine the association between microcephaly and Zika virus infection. Findings: We screened neonates born between Jan 15 and Nov 30, 2016, and prospectively recruited 91 cases and 173 controls. In 32 (35%) cases, congenital Zika virus infection was confirmed by laboratory tests and no controls had confirmed Zika virus infections. 69 (83%) of 83 cases with known birthweight were small for gestational age, compared with eight (5%) of 173 controls. The overall matched odds ratio was 73·1 (95% CI 13·0–∞) for microcephaly and Zika virus infection after adjustments. Neither vaccination during pregnancy or use of the larvicide pyriproxyfen was associated with microcephaly. Results of laboratory tests for Zika virus and brain imaging results were available for 79 (87%) cases; within these cases, ten were positive for Zika virus and had cerebral abnormalities, 13 were positive for Zika infection but had no cerebral abnormalities, and 11 were negative for Zika virus but had cerebral abnormalities. Interpretation: The association between microcephaly and congenital Zika virus infection was confirmed. We provide evidence of the absence of an effect of other potential factors, such as exposure to pyriproxyfen or vaccines (tetanus, diphtheria, and acellular pertussis, measles and rubella, or measles, mumps, and rubella) during pregnancy, confirming the findings of an ecological study of pyriproxyfen in Pernambuco and previous studies on the safety of Tdap vaccine administration during pregnancy. Funding: Brazilian Ministry of Health, Pan American Health Organization, and Enhancing Research Activity in Epidemic Situations.